THE RELATIONSHIP BETWEEN YOGA EXERCISE AND MOTHER'S WEIGHT GAIN DURING PREGNANCY AT PMB RUFINA SURAKARTA - Putriningrum, Rahajeng; Umarianti, Tresia; Sri Harti, Agnes; Yessy Maretta, Megayana (Jurnal Kesehatan Kusuma Husada, 2025)
Pregnant women are people who really need attention, where this attention is needed to look after small creatures who are a gift from Allah SWT. During this period, pregnant women experience many changes. Physical and psychological changes. Physical changes include the increase in body composition of pregnant women due to the presence of the fetus and hormonal changes, so the mother's weight also increases during pregnancy. This activity aims to provide community service to empower pregnant women to reduce anxiety levels through yoga. . The method used is Participatory Action Research where community service aims to provide learning in overcoming problems. This is done by practicing together with pregnant women and detecting the anxiety level of pregnant women through questionnaires. Community service implementation was carried out in Grogol Village in April-May 2024 for 28 pregnant women with a decrease in anxiety in pregnant women after giving Yoga. The results of community service by providing yoga to pregnant women showed an anxiety score from an average of 32.68 to 12.07